The Paradigm of Criminal Offences Becoming Ordinary Criminal Offences in Cases of Sexual Harassment Within the Family as a Form of Criminal Law Reform in Indonesia - Grace Yurico Bawole; Wulanmas Frederik; Emma V. T. Senewe; Natalia Lengkong (Inovasi Pratama Internasional. Ltd, 2026)
The purpose of this study is to find the ideal concept of regulating complaint offences into ordinary offences against the enforcement of sexual harassment cases in the household as a form of legal reform in Indonesia, using empirical juridical research methods. The research method uses an approach that examines the applicable legal rules in the social, political, economic, and cultural contexts, as well as to understand how the law works in everyday reality. This research is essentially normative legal research but is also supported by empirical research. There are many cases of sexual abuse in Indonesia, but it is still very difficult to enforce the law because sexual abuse within the household is still considered a complaint offence. so that law enforcement officials cannot prosecute and punish perpetrators if there is no report or complaint from the victim, or even if there is a complaint and report, the victim usually reconciles with the perpetrator and the legal process is terminated because it cannot be continued. Therefore, it is necessary to reclassify offences from complaint-based offences to ordinary offences in cases of sexual abuse within the household as a form of criminal law reform in Indonesia.